Density Valley Clustering Reveals New Swim Types of the Zebrafish Larvae - Marques, João Carlos Bento (2018)
The ultimate function of the nervous system is to produce behaviours that enable animals to survive and reproduce. Accordingly, if we want to understand how the brain works it is crucial to take into account its final output. Ethology postulates that complex behaviours are formed by sequences of simpler units of movements. The identification and characterization of these behavioural motifs could be useful to understand how the neuronal circuits that underlay them work.